Quasihomogeneous model of gas-dispensed flows with chemical reactions and phase transitions - Timoshenko, V.I. (Reports of the National Academy of Sciences of Ukraine, 2018)
The formulation and description of a quasihomogeneous mathematical model of gas-dispersed flows in the presence of a nonequilibrium gas-phase and heterogeneous chemical reactions is given. The case where, in addition to fine particles, relatively large particles of a dispersed phase are present in a quasihomogeneous gas-dispersed mixture is considered.